1973
DOI: 10.2307/2345108
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Computers on the Teaching of Statistics

Abstract: Summary The influence of computers on the teaching of statistics at university level is surveyed by considering recent research which, by virtue of its use of the immense power of modern computers, has radically transformed statistical practice and which, in turn, is modifying what and how we teach statistics to the next generation of statisticians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…falls to specified percentages of the maximum value, from which we see that the likelihood surface is very flat. A computer program for plotting a function of two variables is described by Evans (1973), and has been extended by him to plot in a triangular co-ordinate system. Maximum likelihood estimates may be calculated by using a simplex procedure of function minimization (O'Neill, 1971).…”
Section: Applicationsmentioning
confidence: 99%
“…falls to specified percentages of the maximum value, from which we see that the likelihood surface is very flat. A computer program for plotting a function of two variables is described by Evans (1973), and has been extended by him to plot in a triangular co-ordinate system. Maximum likelihood estimates may be calculated by using a simplex procedure of function minimization (O'Neill, 1971).…”
Section: Applicationsmentioning
confidence: 99%
“…Not everyone was convinced of the pedagogical merits of this development. At a meeting of the Royal Statistical Society in November 1972 my former Newcastle University colleague Dr Dennis Evans, an early advocate for the use of computers in the teaching of statistical methods, could not hide his frustration in responding to one of the discussants of his paper (Evans, ), remarking that…”
Section: Statistics and Information Technology: A Very Short Historymentioning
confidence: 99%
“…Not everyone was convinced of the pedagogical merits of this development. At a meeting of the Royal Statistical Society in November 1972 my former Newcastle University colleague Dr Dennis Evans, an early advocate for the use of computers in the teaching of statistical methods, could not hide his frustration in responding to one of the discussants of his paper (Evans, 1973), remarking that 'I would like to take issue with : : : when he assures us that students understand more about multiple regression when they invert a 5 × 5 matrix using a desk calculator rather than a computer package'.…”
Section: Statistics and Information Technology: A Very Short Historymentioning
confidence: 99%
“…At the very beginning of the computer era, many people had doubtes in the effectiveness of applying computer facilities in classroom teaching on campus. Previous study showed that more and more computer facilities and programs had been adapted in classroom teaching, especially for teaching statistics (Evans, 1973). A previous survey concluded that more than 86% of the schools have used computer facilities in teaching statistics in the M.B.A.…”
Section: Introductionmentioning
confidence: 99%